Advancements in Environmentally Friendly Lubricant Technologies: Towards Sustainable Performance and Efficiency - Iwona Wilińska; Sabina Wilkanowicz (Energies)
The advancement of next-generation lubricants is pivotal for enhancing energy efficiency and mitigating environmental impacts across diverse industrial applications. This review systematically examines recent developments in lubricant technologies, with a particular focus on sustainable strategies incorporating bio-based feedstocks, nanostructured additives, and hybrid formulations. These innovations are designed to reduce friction and wear, decrease energy consumption, and prolong the operational lifespan of mechanical systems. A critical assessment of tribological behavior, environmental compatibility, and functional performance is presented. Furthermore, the integration of artificial intelligence (AI) into lubricant formulation and performance prediction is explored, highlighting its potential to accelerate development cycles and enable application-specific optimization through data-driven approaches. The findings emphasize the strategic role of eco-innovative lubricants in supporting low-carbon technologies and facilitating the transition toward sustainable energy systems.